2012
DOI: 10.6026/97320630008255
|View full text |Cite
|
Sign up to set email alerts
|

Microsatellite analysis in organelle genomes of Chlorophyta

Abstract: Simple Sequence Repeats (SSRs) or microsatellites constitute a significant portion of genomes however; their significance in organellar genomes has not been completely understood. The availability of organelle genome sequences allows us to understand the organization of SSRs in their genic and intergenic regions. In the present work, SSRs were identified and categorized in 14 mitochondrial and 22 chloroplast genomes of algal species belonging to Chlorophyta. Based on the study, it was observed that number of S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
4
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 12 publications
(18 reference statements)
3
4
1
Order By: Relevance
“…For dinucleotide repeats, AT/TA motif was the most common dinucleotide repeat with a frequency of 83.9%. These results are in agreement with previous findings (Gandhi et al 2010;Rajendrakumar et al 2007;Kuntal et al 2012). The higher AT/TA frequencies in chloroplast genomes can be explained to be the conclusion of the high A/T content of the genomes.…”
Section: Distribution Of Cpssrssupporting
confidence: 93%
See 1 more Smart Citation
“…For dinucleotide repeats, AT/TA motif was the most common dinucleotide repeat with a frequency of 83.9%. These results are in agreement with previous findings (Gandhi et al 2010;Rajendrakumar et al 2007;Kuntal et al 2012). The higher AT/TA frequencies in chloroplast genomes can be explained to be the conclusion of the high A/T content of the genomes.…”
Section: Distribution Of Cpssrssupporting
confidence: 93%
“…The higher AT/TA frequencies in chloroplast genomes can be explained to be the conclusion of the high A/T content of the genomes. Among the trinucleotide repeats, AAG/CTT motif was the most common (28.9%) followed by AAT/TTA (24.9%) and AAC/GTT (16%) and this finding was not consistent with earlier studies results (Rajendrakumar et al 2007;Melotto-passarin et al 2011;Kuntal et al 2012). In tetranucleotide SSR motifs, the maximum frequency of 47.1% was showed by AAAG/CTTT followed by AAAT/ATTT (29.4%).…”
Section: Distribution Of Cpssrscontrasting
confidence: 66%
“…Complete mitochondrial genome sequence of the Haberlea rhodopensis are composed primarily of AT/AT and the rest of SRRs have a high content of A/T. These observations confirm other studies that polyA and polyT repeats are found in the mt genomes (Kuntal et al, 2012).…”
Section: Srrssupporting
confidence: 89%
“…Moreover a specific poly (A) 12 mononucleotide genic sequence located in rps3 was found specifically in CCMP531 mt genome. SSRs offer potential advantage for strain discrimination as they are locus-specific, PCR-friendly and highly polymorphic [72]. Thus the three specific SSRs identified can be used to identify CCMP531 and IMET1.…”
Section: Resultsmentioning
confidence: 99%